KEHAMILAN DENGAN GANGGUAN JIWA - Desmiwarti Desmiwarti (Andalas Obstetrics And Gynecology Journal, 2019)
Pregnancy is a dramatic episode of the biological and psychological changes and adaptations of a woman who never experienced it. The incidence of mental disorders in pregnancy was lower than postpartum and outside of pregnancy with 10 - 15% on post partum 10-15% and 2-7% beyond pregnancy. However Ohara reported that 10% of pregnant women was eligible if diagnosed with major and minor depression. There are two phases of pharma- cological management is described in the guidelines panel: the acute phase, symptoms are treated, drug dosage adjusted to prevent the adverse effects and patient given counseling, severe phase, patients were monitored at an effective dose to prevent relapse . In the maintenance phase, patients at risk for relapse is often still treated with medicines. Reported here the case of a female patient aged 31 years diagnosed with G2P1A0H1 term gravid 37- 38 weeks + bipolar affective disorder, current episode manic with psychotic symptoms. Patients have been known to suffer from a mental disorder since 2000 and has been submitted to psychiatry ward for as much as 9 times. Trigger disorder is unknown at this time, the patient suddenly angry for no apparent reason. Patients treated with pharmacotherapy of haloperidol 2x2 mg, roboransia and psychotherapy. Treatments including consideration of the patient to provide pharmacological therapy in a minimun dosage and psychotherapy to effectively reduce teratogenic risk to the fetus. Patients have been known to suffer from a mental disorder since 2000 and has been submitted to psychiatry ward for as much as 9 times. Trigger disorder is unknown at this time, the patient suddenly angry for no apparent reason. Patients treated with pharmacotherapy of haloperidol 2x2 mg, roboransia and psychotherapy. Treatments including consideration of the patient to provide pharmacological therapy in a minimun dosage and psychotherapy to effectively reduce teratogenic risk to the fetus. Patients have been known to suffer from a mental disorder since 2000 and has been submitted to psychiatry ward for as much as 9 times. Trigger disorder is unknown at this time, the patient suddenly angry for no apparent reason. Patients treated with pharmacotherapy of haloperidol 2x2 mg, roboransia and psychotherapy. Treatments including consideration of the patient to provide pharmacological therapy in a minimun dosage and psychotherapy to effectively reduce teratogenic risk to the fetus.Keywords: Mental disorders, bipolar affective disorder, pregnancy, psychotherapy